Species Diversity of Trees and The Usage of The Forest Area Community of The Tai-Lao Conservation of Wat Prum Pra Tan, Ban Nam Kam, Tambon Non Chai Si, Phon Thong District, Roi Et Province - จันทร์สองดวง เอื้อมพร (Community and Social Development Journal, 2018)
Abstract Species diversity of trees was surveyed for, important value index was calculated, and usages of plants among Tai-Lao communities in conservation forest area of Wat Prum Pra Tan, Ban Nam Kam, Tambon Non Chai Si, Phon Phong District, Roi Et province were enumerated. Field survey was conducted from October 2015 – March 2016. The results found 64 species belonging to 56 genera 28 families. The majority family was Fabaceae (9 species) and Annonaceae (6 species). Shorea roxburghii G. Don had 24% of the highest Important Value Index (IVI) and Shorea xylocarpa (Roxb.) Taub. had 23.84%. Shannon Weiner’s Index (H’) of the forest was 3.35. Tai-Lao communities around this forest were interviewed with 30 people on the usage of tree species. The usage of plants was classified into 4 types. Fuel plants had the highest species number with 53 species (82.8%), followed by medicine 45 species (70.3%), structure 40 species (62.5%) and food 22 species (34.4%). Stem was the most used part with 55 species (85.9%), followed by fruit 23 species (35.9%), root 14 species (21.9%), leaf 14 species (21.9%), flower 4 species (6.2%), sap 3 species (4.7%) and shoot 1 species (1.6%). Dillennia obovata (Blume) Hoogland, Tamarindus indica L., Syzygium gratum (Wight) S.N. Mitra were almost used in all parts. The results of this study will be shared to surrounding communities for realize the important and long term sustainable used of natural forest in the conservation forest area of Wat Prum Pra Tan.